2007
DOI: 10.4081/ijas.2007.s2.1260
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rearing system on behavioural and immune responses of buffalo heifers

Abstract: From November 2005 to October 2006 thirty-two buffalo heifers from the same commercial farm were used to evaluate the effect of rearing system on a range of behavioural and immune variables. Sixteen heifers were group-housed in indoor slatted floor pen (3.0 m2/animal) with an outdoor paddock (3.0 m2/animal) at ~5m above sea level (group IR). Sixteen others were kept at ~600m above sea level. They grazed a fenced Mediterranean maquis of ~40ha (group ER). At the end of the experimental period the animals were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 1 publication
2
8
0
4
Order By: Relevance
“…However, this longer duration of immune efficiency compared to the shorter one recorded in this study can be attributed to the higher time spent grazing (24 h) by young bulls [5]. Instead, the cell-mediated response to the skin test recorded in G cows expresses their better immune status, and is consistent with previous studies that have compared grazing and confined animals of different ruminant species [5,30,31,32].…”
Section: Discussionsupporting
confidence: 89%
“…However, this longer duration of immune efficiency compared to the shorter one recorded in this study can be attributed to the higher time spent grazing (24 h) by young bulls [5]. Instead, the cell-mediated response to the skin test recorded in G cows expresses their better immune status, and is consistent with previous studies that have compared grazing and confined animals of different ruminant species [5,30,31,32].…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were obtained in different ruminant species such as sheep (Braghieri et al, 2007) and buffaloes (De Rosa et al, 2007) in which grazing animals showed higher skin thickening as compared with C animals.…”
Section: Immune Responsessupporting
confidence: 83%
“…Although some studies assessed the effect of a pool or potholes on behavior and immunity of buffalo heifers (De Rosa et al, 2007) and on buffalo cow reproduction (Di Palo et al, 2001;Zicarelli et al, 2001), behavior (Tripaldi et al, 2004), and metabolic profile , they did not consider the relationship with the environmental temperatures and the animal's need for thermoregulation. Thus, the present study aimed to verify the effect of 2 housing systems (with and without a pool and an ample outdoor paddock) on the behavior, reproductive performance, and milk yield of buffalo cows in relation to the surrounding temperature.…”
Section: Introductionmentioning
confidence: 99%